Control, Utility and Formalization at the "Frontier": Contested Discourses on Agriculture in Eastern Colombia (Alternautas, 2022)
This article explores the deep transformation of the Altillanura region in Colombia, where the expansion of the agricultural frontier has brought to light the dynamics of the ‘economies of dispossession and land appropriation’ (Jenss, 2017, this issue) that underpin the extractive model dominating Colombian development. Alke offers an overview of the principal mechanisms through which these dynamics are expressed, particularly the expansion of new ‘Economic Zones’ of production and the growth of large-scale plantations which are institutionalised through the pervasive development plans and legislation. The tensions around traditional forms of land tenure and the necessity to offer ‘clear’ property rights to encourage investments in the Altillanura region clearly demonstrate the key tensions in the region, where small farmers and indigenous communities’ clash with large transnational corporations over the expansion of the agricultural frontier.